Everyday life and the sacred : re/configuring gender studies in religion - Berlis, Angela, 1962-; Korte, Anne-Marie, 1957-; Biezeveld, Kune, 1948- (Studies in Theology and Religion, 2017)
An interdisciplinary gender-sensitive approach toward perspectives on the everyday and the sacred are the hallmark of this volume. Looking beyond the dualistic status-quo, the authors probe the categories, textures, powers, and practices that define how we experience, embody, and understand religion and the sacred, their interconnection, but also disassociation with the secular. Contributions by an international group of feminist theologians and religious studies scholars aim to re-configure the study of both religion and gender: Angela Berlis, Anne-Marie Korte, Kune Biezeveld †, Helga Kuhlmann, Maaike de Haardt, Akke van der Kooi, Dorothea Erbele-Küster, Willien van Wieringen, Magda Misset-van de Weg, Gé Speelman, Mathilde van Dijk, Jacqueline Borsje, Hedwig Meyer-Wilmes, Goedroen Juchtmans, Alma Lanser and Riet Bons-Storm.